2022
DOI: 10.31557/apjcp.2022.23.12.4315
|View full text |Cite
|
Sign up to set email alerts
|

Oral Squamous Cell Carcinoma-Derived ANGPTL3 Induces Cancer Associated Fibroblastic Phenotypes in Surrounding Fibroblasts

Abstract: (12), 4315-4322 Grivennikov, 2019). Transforming growth factor-beta (TGF-β), Interleukin(IL)-6 and IL-8, secreted from CAFs, which are typically secreted by CAFs, form the tumor-promoting microenvironment in oral squamous cell carcinoma (OSCC) progression, including proliferation, angiogenesis, and invasion (Ayob and Ramasamy, 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, it has been shown that ANGPTL3 is highly expressed in hepatocellular carcinoma, 158 ovarian cancer, 159 and oral squamous cell carcinoma, 149 which may be related to the fact that ANGPTL3 induces cancer-associated fibroblasts differentiation. 158,160…”
Section: Structure and Function Of Angptl3mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that ANGPTL3 is highly expressed in hepatocellular carcinoma, 158 ovarian cancer, 159 and oral squamous cell carcinoma, 149 which may be related to the fact that ANGPTL3 induces cancer-associated fibroblasts differentiation. 158,160…”
Section: Structure and Function Of Angptl3mentioning
confidence: 99%
“…Furthermore, ANGPTL3 expression is elevated in the livers of NAFLD patients, 149,157 and its inhibitors have the potential to mitigate the progression of NAFLD and provide promising therapeutic approaches for NAFLD. In addition, it has been shown that ANGPTL3 is highly expressed in hepatocellular carcinoma, 158 ovarian cancer, 159 and oral squamous cell carcinoma, 149 which may be related to the fact that ANGPTL3 induces cancer‐associated fibroblasts differentiation 158,160 …”
Section: Drug Development Of Targets Based On Gwas Wgs and Wes Discov...mentioning
confidence: 99%
“…Another study observed elevated levels of GRO-α and tumor-promoting interleukins corresponding to the expression of angiopoietin-like protein. This can in turn induce CAF-like phenotypes within the stromal fibroblasts of OSCC cells and increase the levels of CAF markers, a-SMA and FAP, making this a potential quarry for targeted therapies in the future ( 105 ).…”
Section: Extrinsic Factors Governing Oscc Stemnessmentioning
confidence: 99%